Effect of Interaction BetwÂ·een Phosphorus and Zink in Some Morphological Features of Two Varieties of Wheat Grown in Gypsum Soil - -Mahmod, A. A.; Al-Saidi, A. J. H .; Saltern, K. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A  biological   experirne.rit   was  CQhducted Â·ll1  the   (Ibn-  AlÂHaitham).  University        of   Baghdad  for   growing   seasens   on   of2004/2005 (by using gypsum soil taken from Al- Doar area I Salah AlÂ Dean provinc)  to stuclÂ·- the effect three levels of phosphorus (0, 400,SOO)rng ! pot and four  levels of zinc (0, 10,.. J 5, 2.0) tngf I pot on somefeatures of two  varieties -Qf    wheat, (triticum aestivurn var. rateh)and(Triticum aestiv1lm Var. Ipa 99)..R't:sul.ts  o:f experiment showed  comparative  wheat  verities in those features studied  under gypsum soil c.onditic)n  1n a way that AIÂ Fateb  varie.ty  was superior on  lpa 99 in feature Qf  dty  weight  leave areas, absolute growth rate,. relative product anrelative efficiency of fertilizer The r sults also showed                   negative effect of high levels of pbosphqrus .-anzinc  on  the  most  of :patmears studied  at  the  two varieties.